Work Engagement, Self Efficacy and Job Satisfaction of Professional Educators - Trisnadi Tarigan; Dimyati Dimyati (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
Teachers as professional educators have an important role in developing human resources. The task of the teacher is not only as a teacher but also as an educator, so that in addition to having the task of strengthening the intellectual capacity of students, it is also responsible for the formation and development of the personality capacity and abilities of students cognitively, affective and psychomotor. However, apart from these assignments, teachers still have various problems related to excessive workloads and quality demands that are not comparable to the economic and social welfare they receive and problems with politicization of teachers. This problem simultaneously affects work engagement, self-efficacy and job satisfaction of professional educators. Even though work engagement.